2017
DOI: 10.20473/jn.v12i1.3448
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Fruit and Vegetable with Risk of Obesity in School-Age Children

Abstract: Introduction:The problem of obesity in children aged 5-12 years in Indonesia is still high, East Java is one of the provinces that have higher prevalence of obesity than the national average (Riskesdas 2013). Consumption of fruit and vegetables affects the level of obesity's risk, but nowadays fruit and vegetable consumption in school-age children are low. This study was aimed to determine the correlation between consumption patterns of fruits and vegetables with the risk of obesity in school-age children in K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
(3 reference statements)
0
2
0
2
Order By: Relevance
“…21 Consumption of fruits and vegetables has the potential to mitigate the prevalence of obesity in youngsters, as these food groups possess the ability to facilitate fat oxidation while containing relatively low caloric content. 22 Other research done in the United Kingdom examined the potential benefits of consuming a nutritious diet, namely one that includes fruits and vegetables, in reducing obesity and overweight in youngsters. 7 The results showed a decline in the prevalence of television viewing and the level of exposure to computer or video games after six months of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…21 Consumption of fruits and vegetables has the potential to mitigate the prevalence of obesity in youngsters, as these food groups possess the ability to facilitate fat oxidation while containing relatively low caloric content. 22 Other research done in the United Kingdom examined the potential benefits of consuming a nutritious diet, namely one that includes fruits and vegetables, in reducing obesity and overweight in youngsters. 7 The results showed a decline in the prevalence of television viewing and the level of exposure to computer or video games after six months of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Konsumsi sayur dan buah yang rendah dapat menyebabkan beberapa masalah gizi pada anak, salah satunya adalah obesitas pada anak usia sekolah (Anggraeni, 2016). Hasil penelitian yang dilakukan oleh Siagian, dkk.…”
Section: Pendahuluanunclassified
“…In Germany, a cohort study showed that adequate FVC suppressed the increases in students' body mass index (Bayer et al, 2014). In East Java, Indonesia, a study found that FVC below the recommended level is associated with a higher risk of obesity among elementary school students (Anggraeni et al, 2017). Moreover, FVC is also associated with food choices, where children who have more FVC are more likely to eat a greater variety of foods with healthier food choices (Korinek et al, 2015).…”
Section: Introductionmentioning
confidence: 99%